Analisis Tingkat Kemampuan Literasi Digital Pemasaran (Digital Marketing) Menggunakan Metode Experiential Learning pada Mahasiswa Perhotelan Politeknik Harapan Bersama - Wiyanti Wiyanti; Ratri Wikaningtyas (Dharma Ekonomi, 2024)
This study is titled "Analysis of the Level of Digital Marketing Literacy Using the Experiential Learning Method Among Hospitality Students at Politeknik Harapan Bersama." The objective of this research is to evaluate and understand the level of digital marketing literacy possessed by hospitality students at Politeknik Harapan Bersama across various aspects, including the use of information technology, digital communication, online collaboration, and data security. This study employs a quantitative approach using a survey method, with questionnaires distributed to 26 students. The findings indicate that most students have an excellent level of digital marketing literacy, with an average percentage of 84.78%. However, there are still areas that need improvement, such as understanding digital ethics and selecting valid information. These findings provide valuable insights for developing more effective training programs to enhance digital skills in Hospitality Study Program.